MONEY LAUNDERING: HOW IT BECOMES AN INTERNATIONAL THREAT (RESPONSE AGAINST MONEY LAUNDERING FROM THE SIDE OF INDONESIA) - Kurniasari, Eka (Indonesian Journal of International Law, 2014)
Money Laundering is one of the transnational organized crime which has been increasing intensively. Money laundering is the term used to describe a process of concealing the source of money that gained through crime (it is usually called “dirty money”). This process is done with the aim to make the “dirty money” converted into “clean money”. There are many ways for this process to be done, among them is by buying properties and houses. Other is by saving the “dirty money” in a bank account that will later turned it into “clean money”. This is where the bank service could get involved in this particular crime. In an attempt to overcome this problem, countries joining in the G-7 Summit established the Financial Action Task Force (FATF) in Paris in July 1989 that provides standards recommendation, national and international, as measures to make integrated cooperation among countries. This essay discusses the very definition of money laundering, the role FATF takes in order to prevent money laundering, and the responses of Indonesia regarding money laundering.